Criminal Sanctions for Traffic Negligence Resulting in Death: Perspectives of Positive Law and Islamic Law - Laila, Siti Afifi Nur; Musyafa’ah, Nur Lailatul (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Negligence in traffic that results in death is a form of criminal act that often occurs in the life of modern society. These events are generally not carried out with an element of intention, but the consequences, including loss of life, make them acts that must be legally accounted for. This study aims to analyze the concept of sanctions and accountability for traffic negligence that causes death from the perspective of positive law and Islamic law. The research method used is normative legal research with a statutory approach and a conceptual approach. The data sources used are primary, secondary, and tertiary legal materials that are analyzed qualitatively. The results of the study show that, under Indonesian law, negligence resulting in death is regulated by the Criminal Code and Law Number 22 of 2009 concerning Road Traffic and Transportation. The sanctions imposed on the perpetrators are either imprisonment or fines, intended to deter, protect the community, and uphold law and order. Meanwhile, in Islamic law, acts that cause death due to negligence are categorized as qatl al-khaṭa’. Accountability in this concept is not only in the form of social sanctions, but also includes the obligation to pay diyāt to the victim’s family and the implementation of kafārah as a form of spiritual responsibility to Allah SWT. These differences show that positive law focuses more on the criminal aspect, while Islamic law combines aspects of justice for the victim, the moral responsibility of the perpetrator, and the spiritual dimension. Thus, both legal systems place the protection of human life as the main principle in law enforcement.